New trends in science, technology and innovation policy development to promote green growth and sustainable development - Dang Thu Giang; Cao The Anh; Duong Kieu Trinh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Science, technology and innovation (STI) are key elements in ensuring and promoting green growth and sustainable development. Despite this, the world continues to face persistent challenges in energy, climate change, and environmental risks to people’s health and well-being, while rapid technological advancements introduce new risks and uncertainties. Therefore, the problem for STI policymakers is to promote economic growth while minimizing the unwanted impacts of STIs on the environment and social security, with the core motto “leaving no one behind”. This article aims to understand the trends of the STI policy development in the world in the context of green growth, and sustainable development thereby linking it to Vietnam and identifying the problems posed to it. The article comprises four sections: (1) Trends in green growth, and sustainable development and the role of STI; (2) Green growth and sustainable development requirements for the STI policy development; (3) New trends in the STI policy development in the context of green growth and sustainable development; (4) Implications for STI policy development in Vietnam. Code: 24091601